Simulation of Surface Settlement Induced by Parallel Mechanised Tunnelling - Huat, Chia Yu; Danial Jahed, Armaghani; Lai, Sai Hin; Haleh, Rasekh; He, Xuzhen (MDPI, 2023)
Mechanised tunnelling is extensively utilised for twin tunnel construction, particularly in urban areas. A common challenge encountered during this construction method is the occurrence of surface settlement (SS) induced by tunnelling activities. The integrity of nearby structures can be compromised by SS, making it imperative to accurately quantify and mitigate this phenomenon. Several methods for determining SS exist, including empirical formulas and laboratory studies. However, these methods are often constrained by specific soil types and are time-consuming. Moreover, crucial parameters such as tunnel operational factors and construction stages are often omitted from empirical formulas. Given these limitations, this paper aims to address these challenges by employing 3D numerical analysis to simulate tunnelling-induced SS in twin tunnels. This approach takes into account tunnel geometry, construction sequencing, soil properties, and tunnelling operational factors. By incorporating data from in-situ and laboratory tests conducted on the ground, engineering soil parameters are established as inputs for the numerical analysis. The simulated SS results obtained from the 3D numerical analysis are compared with field measurements of SS taken from available ground surface settlement markers. The transverse SS pattern derived from the numerical analysis closely mirrors the field measurements. Additionally, SS values above the first and second tunnels are compared with field measurements, resulting in coefficient of determination (R2 ) values of 0.94 and 0.96, respectively. The utilisation of the 3D numerical modelling approach enables the customizable mitigation strategies for managing the SS with project-specific parameters such as tunnel geometry, geotechnical engineering factors, and tunnelling operational variables. This will help plan and construct more sustainable tunnels with minimal effects on the ground and residential areas.